Unsaid known in the boardroom: theorizing unspoken assessments of behavioral board dynamics - Engbers, Marilieke; Khapova, Svetlana N.; van de Loo, Erik (Frontiers in Communication, 2024)
Effective board performance relies heavily on the smooth exchange of information and knowledge among members. However, the sociocognitive processes surrounding these information exchanges within boards, known as board dynamics, are often treated as a black box in corporate governance research. With the goal of advancing the understanding of communication-centered board dynamics, this paper develops a theoretical model of unsaid known in the boardroom. Drawing on the communication, psycho-dynamics, and governance literature, we theorize how board members jointly make sense through what they think and say and not say and offer propositions. We discern between the implicit theories of senders and listeners, shaping decision-making. Our conceptual model suggests that heightened collective awareness among board members regarding communication incongruences can improve decision-making. Addressing these discrepancies can enhance boards' capacity for informed decision-making and optimize outcomes.